The Impact of Inflation on Foreign Direct investment (FDI): Evidence from Bangladesh - Alam, Md Rokibul (My University, 2025)
This study investigates the impact and relationship of inflation on foreign direct investment (FDI) inflows in Bangladesh over the period 1987–2024. To do so, the study adopts a quantitative, time-series design using annual data from the World Bank, Bangladesh Bank, and IMF. Furthermore, the analysis employs econometric techniques, including the Augmented Dickey–Fuller and Phillips–Perron tests, Johansen cointegration, Vector Error Correction Model (VECM), and Ordinary Least Squares (OLS) regression to determine both short- and long-run dynamics among FDI, inflation, GDP growth, and interest rates. The finding of the study confirms the existence of a long-run equilibrium relationship among the variables, implying that FDI, inflation, and growth move together over time. The normalised cointegrating equation reveals that GDP growth, inflation rate and interest rates exert positive effects on FDI in the long run. In addition, the VECM results show that approximately 14.8 % of disequilibrium in FDI is corrected annually toward long-run equilibrium, indicating a moderate speed of adjustment. The findings of the study also ensured that in the short run, inflation and interest rate fluctuations are statistically insignificant, suggesting that investors respond more to long-term macroeconomic stability than to temporary price changes. The OLS robustness test further supports that GDP growth is the strongest determinant of FDI inflows, while moderate inflation does not significantly deter investment as long as it remains predictable. Overall, the findings emphasise that Bangladesh’s ability to sustain FDI depends on maintaining price stability, credible monetary policy, and consistent economic growth. Policy recommendations include strengthening inflation-targeting frameworks, improving central-bank transparency, and fostering GDP-driven productivity growth to enhance investor confidence and ensure resilient capital inflows.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance